Impact of COVID-19 on the future of cadaveric dissection and anatomy teaching - Karkera, Shilpa (International Journal of Research in Medical Sciences, 2021)
The COVID 19 pandemic has left a major impact on medical education globally. We are undergoing crisis for humanity with this virus causing extensive damage to life and its aspects. Hence, we do not know how this will unfold in upcoming year. All the academic classes are suspended during nationwide lockdown to ease the propagation. It is high time to rethink ways to deliver quality medical education under restriction of social distancing in real time teachings and discussions. We propose based upon our experiences, replacement of anatomy dissection with virtual dissection and its implications. It has its own challenges which could overcome with the planned directives based upon current experience.